Partial OFDM demodulation for frequency syntonization of Wireless Sensor Nodes - Tröger, Hans-Martin; Robert, Jörg; Keppeler, Martin; Hartmann, Markus; Heuberger, Albert (9th International IEEE Symposium on Precision Clock Synchronization for Measurement, Control, and Communication, ISPCS 2015, 2015)
Synchronization of a Wireless Sensor Network is a crucial task and is based on a precise syntonization of all clocks within the network. The synchronization precision is usually closely connected to the positioning accuracy in networks for the purpose of localization. This paper introduces a concept, how the clocks of low-complexity stationary receivers can be adjusted to the same frequency with the help of a television broadcast signal. Only parts of the signal information are used to achieve a manageable data rate for the embedded low-power processor. With a new algorithm the performance of the frequency estimation can be kept high compared to the use of the total signal energy, while the processing load can be reduced dramatically.
Keywords: localization; Signals of Opportunity; synchronization; syntonization; tracking loop